A case of unrecognized psychogenic polydipsia - Chong, Seng Choi; Ibrahim, Normala (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Psychogenic polydipsia is prevalent among people with schizophrenia. Although its pathophysiology is relatively unknown, it causes life threatening complications due to acute or severe hyponatraemia.. This report illustrates a patient with schizophrenia who had unrecognized psychogenic polydipsia and developed severe complication. It also highlights the clinical salience of its management.